FEASIBILITY STUDY OF TREATING CHEMICAL FERTILIZER WASTEWATER USING BENCH SCALE EXTENDED AERATION ACTIVATED SLUDGE SYSTEM - MD HAFIZ, MOHAMMAD FAKHUMA UBAIDILLAH (2021)
A chemical fertilizer plant in Kedah, Malaysia produced high Ammonia-nitrogen content in the discharge outlet, exceeding the allowable standard limit (Standard B).